Use of complementary and alternative medicine by cancer patients in Colombia - Raúl Murillo; Nidia Pinto-Martínez; Norma Serrano; Claudia Uribe; Edgar Navarro; Jorge Duque; Andrés Yepes; Laura Olaya; Carolina Mariño; Olga Lucia Morales; Marcela Andrea Erazo-Muñoz; Diana Carolina Sánchez-Vega; et al. (BMC, 2023)
Abstract Background The use of complementary and alternative medicines (CAM) among cancer patients varies greatly. The available data suggest an increasing use of CAM over time and a higher prevalence in low- and middle-income countries. However, no reliable data are available from Latin America. Accordingly, we examined the prevalence of CAM use among cancer patients from six Colombian regions. Methods We conducted a survey on cancer patients attending comprehensive cancer centres in six capital cities from different regions. The survey was designed based on a literature review and information gathered through focus groups on CAM terminology in Colombia. Independent random samples of patients from two comprehensive cancer centres in every city were obtained. Patients 18 years and older with a histopathological diagnosis of cancer undergoing active treatment were eligible. The prevalence of CAM use is reported as a percentage with the corresponding confidence interval. CAM types are reported by region. The sociodemographic and clinical characteristics of CAM users and non-users were compared using Chi square and t tests. Results In total, 3117 patients were recruited. The average age 59.6 years old, and 62.8% were female. The prevalence of CAM use was 51.7%, and compared to non-users, CAM users were younger, more frequently women, affiliated with the health insurance plan for low-income populations and non-Catholic. We found no differences regarding the clinical stage or treatment modality, but CAM users reported more treatment-related side effects. The most frequent types of CAM were herbal products, specific foods and vitamins, and individually, soursop was the most frequently used product. Relevant variability between regions was observed regarding the prevalence and type of CAM used (range: 36.6% to 66.7%). The most frequent reason for using CAM was symptom management (30.5%), followed by curative purposes (19.5%). Conclusions The prevalence of CAM use among cancer patients in Colombia is high in general, and variations between regions might be related to differences in cultural backgrounds and access to comprehensive cancer care. The most frequently used CAM products and practices have little scientific support, suggesting the need to enhance integrative oncology research in the country.